Investigating the potential for dual-purpose use in winter oats - Forgács, Fanni Zsuzsa; Virág, István Csaba; Kutasy, Erika Tünde (Acta Agraria Debreceniensis, 2025)
Dual-purpose usage is not a common technology for oats in Hungary, which is not surprising, as the area sown to our main crop is also very low. Yet the crop has a lot of untapped potential, not to mention its excellent nutritional parameters. In our experiment we investigated how much biomass can be expected after mowing winter oats at different phenological stages and whether we can expect a valuable grain yield after this process. Mowing was carried out at one-week intervals on a total of 4 occasions with 2 cutting heights. Plant height and NDVI values of the vegetation in the plots were measured during the experiment. After the harvest of the fully ripened grains, the yield and the thousand kernel weight (TKW) were determined. Our results show that with a lower cutting height (6 cm), a higher biomass yield can be achieved. The cutting height had no statistically verifiable effect on either NDVI or plant height. Droughty weather conditions during subsequent mowing significantly reduced the regeneration capacity of the plants, which was strongly reflected in the measured parameters. Furthermore, a higher grain yield was measured at a cutting height of 9 cm, which decreased gradually with the mowing time. Neither the cutting height nor the mowing time had any effect on the TKW.